2014
DOI: 10.1093/tropej/fmu050
|View full text |Cite
|
Sign up to set email alerts
|

The Upsurge of SSPE--A Reflection of National Measles Immunization Status in Pakistan

Abstract: Subacute sclerosing panencephalitis (SSPE) is a rare disorder in the developed world. However, an upsurge has been seen lately in our part of the world owing to inadequate measles immunization coverage. At the midst of our struggle against polio, we are struggling with the war against other vaccine-preventable childhood illnesses like measles. The increasing numbers of SSPE that we reported over the past half decade suggest an underlying periodic measles epidemic in Pakistan. In addition, children are now pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In the postmeasles vaccination era, another north Indian tertiary care center registered 458 serologically confirmed SSPE cases over a 10‐year period (1996 to 2005) . In Pakistan, from Karachi, 43 patients of SSPE were diagnosed between 2000 and 2012 . In both countries, a large number of SSPE cases are likely to remain unreported.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the postmeasles vaccination era, another north Indian tertiary care center registered 458 serologically confirmed SSPE cases over a 10‐year period (1996 to 2005) . In Pakistan, from Karachi, 43 patients of SSPE were diagnosed between 2000 and 2012 . In both countries, a large number of SSPE cases are likely to remain unreported.…”
Section: Epidemiologymentioning
confidence: 99%
“…8 In Pakistan, from Karachi, 43 patients of SSPE were diagnosed between 2000 and 2012. 9 In both countries, a large number of SSPE cases are likely to remain unreported.…”
Section: Epidemiologymentioning
confidence: 99%
“…Subacute sclerosing panencephalitis, commonly known as SSPE, is a progressive neurodegenerative disease caused by the persistence of measles infection commonly seen in children and young adults. 1 SSPE was previously known as Dawson’s inclusion body encephalitis as Dawson in 1933 and 1934 reported cellular inclusions in the cerebral lesions of patients with SSPE, thus resulting in this disease being labeled as Dawson inclusion body encephalitis. 2 Ten years later, Brain et al 3 reported similar conditions with further case reports, and later, the term SSPE was coined.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with SSPE have a history of primary measles infection at an early age (< 2 years), which continues with latent period of infection. 3,4 Most patients survive 1 to 3 years after diagnosed, with mean survival time is about 18 months. 2 The neurological manifestations that appear will be progressive, and causes the death.…”
Section: Epidemiologymentioning
confidence: 99%